Growth and production of red onion (Allium ascalonicum L.) with the application of monosodium glutamate and endophytic fungi. Issue 1 (May 2021) - Alfiani, A; Haring, F; Syam'un, E
Abstract: This study aimed to reveal the effect of giving monosodium glutamate (MSG) and endophytic fungi ( Trichoderma sp., Mycorrhiza, and Beauveria bassiana ) to red onion ( Allium ascalonicum L.) plants which predicted to increase its growth and production while decrease diseases infection without harming the environment. The experiment was designed by Factorial-Randomized Block Design. There were two factors tested in this present study: (1) MSG treatment with three dosages: 0 g L −1, 5 g L −1, and 10 g L −1 ; (2) endophytic fungi treatments with single or pure culture and mix-culture combinations: Trichoderma sp., Beauveria bassiana, Mycorrhiza, the combination of Trichoderma sp. and Beauveria bassiana, the combination of Trichoderma sp. and Mycorrhiza, the combination of Mycorrhiza and Beauveria bassiana, and the combination of Trichoderma sp., Beauveria bassiana, and Mycorrhiza . The parameters measured were plant growth, harvest, and disease infection intensity. The treatments did not give significant improvement to all parameters. This study concluded that Mycorrhiza treatment produced the highest rate value in red onion harvest.